Research Ethics Module - Junker-Kenny, Maureen; Trinity College Dublin. Irish School of Ecumenics; Trinity College Dublin. School of Religions and Theology (Trinity College Dublin. Long Room Hub, 2008)
Aimed at postgraduate students, the Research Ethics module is run as a Strategic Innovation Fund (SIF) project by TCD's Irish School of Ecumenics and School of Religions and Theology in collaboration with UCC and NUIG. The course offers an opportunity to investigate the ethical aspects and obligations of various fields of research.
Exhibited at the Glucksman Memorial Symposium on June 12th 2008
Keywords: Research -- Ethics; Research methodology